An Isolated Resonant Mode Modular Converter with Flexible Modulation and Variety of Configurations for MVDC Application - Xiang,X; Zhang,X; Chaffey,G; Green,T (IEEE Transactions on Power Delivery, 2017)
The dc tap or dc transformer will play an important role in interfacing different voltages of dc links in dc grids. This paper presents an isolated resonant mode modular converter (RMMC) with flexible modulation and assorted configurations to satisfy a wide variety of interface requirements for medium voltage dc (MVDC) networks. The transformer-less RMMC, as introduced in the literature, implemented a restricted modulation scheme leading to a very limited range of step-ratio and the diode rectifier resulted in unidirectional power flow. Both of these limitations are removed in this proposal and galvanic isolation has also been added. Moreover, this new RMMC approach can serve as a building block for variety of configurations. Two such derived topologies are given, which inherently balance the voltage and current between different constituent circuits and realize the high power rating conversion for very low or very high step-ratio application. The theoretical analysis is validated by a set of full-scale simulations and a down-scaled experimental prototype. The results illustrate that this isolated RMMC and its derivatives have promising features for dc taps or dc transformers in MVDC applications.